Cover Picture: Total Synthesis of Leupyrrins A1 and B1, Highly Potent Antifungal Agents from the Myxobacterium Sorangium cellulosum (Chem. Eur. J. 14/2017). Issue 14 (9th January 2017) - Thiede, Sebastian; Wosniok, Paul R.; Herkommer, Daniel; Debnar, Thomas; Tian, Maoqun; Wang, Tongtong; Schrempp, Michael; Menche, Dirk
Abstract : The total syntheses of leupyrrins A1 and B1, antifungal agents from Sorangium cellulosum, are presented. We associate the building blocks of leupyrrins, being natural products, with the four natural elements—fire, water, air, and earth. These four elements also had a key significance in the synthesis: heating (fire) for the synthesis of the pyrrole fragment, an enzyme‐catalyzed reaction (water) for the butyrolactone, a hydrogenation (air) for the diacid, and the metal Zr (earth) for the diyne. More information can be found in the Full Paper by D. Menche et al. onpage 3300 ff.